How to Win Friends and Trade with People: Southern Inuit, George Cartwright, and Labrador Households, 1763 to 1809 - Hay, Stephen (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2017)
British and Southern Inuit traders in late-18th-century Labrador embedded the fisheries and fur trade in their social relations through transculturation. Specifically, British traders such as Capt. George Cartwright changed how they organized their friendships and households, as did Attuiock, an Inuit angakkuq or shaman. Cartwright’s approach evolved from using “luxury” to try to regulate Inuit workers and traders to also including Inuit traders and workers in his friendships and households. Even if Cartwright misunderstood what this meant to his Inuit partners, this approach made sense to them, too, as they were, after all, also agents of this transculturation.